An Investigation in to the relationship between Iranian EFL Teachers´ Creativity and their Classroom Management Strategy Use - Tashakori, sakine; Mirzaee, Abolghasem; Rahimi, Mohammad; Rahmanian, Mojtaba (IJRDO- Journal of Educational Research, 2018)
This study aimed to explore the potential relationship between teachers' creativity and their classroom management strategy use. In the first phase, two questionnaires (ELTCQ and classroom management strategy use questionnaire) were given to a total of 70 teachers, to determine if there was any relationship between teachers’ creativity and their classroom management strategy use. The findings revealed that there was no significant correlation between teachers’ creativity and their use of “Organizing strategies”, “Teacher-student relationship strategies”, and “Teacher punishment/reward strategies”. Nevertheless, there was a meaningful positive relationship between teachers’ creativity and their “Teaching management strategies”. Moreover, the strength of the correlation between teacher creativity and teaching management strategies was average.